Algebraic number theory - Mollin, Richard A. (Discrete mathematics and its applications, 2011)
"The second edition of this popular book features coverage of L-functions and function fields to provide a more modern view of the field. This edition also introduces class groups for both binary and quadratic forms, making it much easier to prove the finiteness of the class number of both groups via an isomorphism. In addition, the text provides new results on the relationship between quadratic residue symbols and fundamental units of real quadratic fields in conjunction with prime representation. Along with reorganizing and shortening chapters for an easier presentation of material, the author includes updated problem sets and additional examples"--